How Does The Official Indonesian Tourism Website Apply The Dimensions of The Experiential Marketing? - Mwinuka, Nickson Nazarenus; Phabiano, Edward; Sumarwan, Antonius (E-Journal of Tourism, 2024)
This paper aimed to explore out how the dimensions of experiential marketing have been applied in the official Indonesian tourism website.  It is the qualitative paper which basically focuses on content analysis, data were obtained through literature documents (journals and articles) and internet documents. The dimensions discussed on engaging all five senses, creating link with customers, creating surprise, themes the experience (giving a clear message) and memorability. Basing on the way the website operates, the findings show that, the dimensions towards implementing the experiential marketing while promoting and advertising the attractions in Indonesia is fulfilled. The paper shows how the internet revolutionary has changed the way of marketing the tourism products when experiential marketing is well utilized. The purpose of this paper was to find out whether the experiential marketing via website is done right or not and the result showed ,the dimensions are followed and applied but not smarter as it was expected, there is need to have more research which will account how  many consumers visit the destinations due to the role played by the website, to this point the paper can help the academicians to conduce more researches on this point, the government and other policy makers will be helped by the paper to amend and do some improvements on the way of running the website. For example, some of the destinations are not well described, meaning no clear details concerning the destinations especially to the new customers who visit the website for the first time.